The Order of the Learning Spaces to Increase Learning Spirits at Madrasah Tsanawiyah Nurul Islam Surabaya - Muchlisiniyati Safeyah; Wiwik Dwi Susanti (Nusantara Science and Technology Proceedings)
The success of teaching and learning process depends not only on the teacher's expertise but also influenced by the condition of the learning space. The structures of the learning space must pay attention to the factors of flexibility, achievement, flexibility, comfort, and beauty can increase the spirit for students and teachers to transfer knowledge. The classroom and library room at MTs Nurul Islam pay less attention to flexibility and beauty factor. The purpose of the program is to improve the classroom and library of MTs Nurul Islam Surabaya so that it can improve the spirit of learning and teaching for students and teachers. The method is done through counseling and setting practice. The results of the counseling it can motivate teachers to apply a seat arrangement pattern that adjusted the learning activities. Furthermore in one of the classroom also was done by painting with dark green and light green. The dark green and light green colors are selected which are brighter than the previous ones. The arrangement of wall color is also made different, is two side wall of dark green and two sides wall with light green color. The Floor in the library room raised ± 20 cm to overcome the flood.